Sociodemographic and behavioral influences on multimorbidity among adult residents of northeastern China - Jikang Shi; Yanbo Guo; Zhen Li; Zhuoshuai Liang; Lingfeng Pan; Yang Yu; Wenfei Zhu; Aiyu Shao; Wenjun Chen; Chao Gao; Siyu Liu; Yawen Liu; et al. (BMC, 2022)
Abstract Background Multimorbidity is defined as two or more chronic health conditions existing in an individual simultaneously. Multimorbidity has been associated with poor conditions, such as higher health care costs and the poor quality of life. Thus, identifying the risk factors of the multimorbidity is required for multimorbidity prevention. Methods This study was based on the Comprehensive Demonstration Research Project of Major Chronic Noncommunicable Disease Prevention and Control Technology in Northeast China initiated by China Medical University. The investigation was a cross-sectional study under a multistage stratified cluster random sampling design. Associations between multimorbidity and sociodemographic and behavioral factors in adult residents were investigated using univariate analysis and multivariate logistic regression analysis. Results A total of 6706 participants were enrolled in this investigation, and the prevalence of multimorbidity was 21.2% among the adult residents of northeastern China. There existed differences of association between age and multimorbidity risks (65-69 years old: OR = 3.53, 95%CI: 2.04-6.12; 70-74 years old: OR = 5.26, 95%CI: 3.02-9.17). Participants who are overweight had significantly high multimorbidity risk (OR = 2.76, 95%CI: 1.50-5.24). Family history of hypertension and family history of diabetes were significantly associated with high multimorbidity risk (family history of hypertension: OR = 2.34, 95%CI: 1.96-2.79; family history of diabetes: OR = 1.77, 95%CI: 1.38-2.26). Compared with the frequency of fatigue (< 1 time/week or 1-2 times/week), that (≥3 times/week) was associated with high multimorbidity risk (OR = 1.39, 95%CI: 1.07-1.81). For fresh fruit consumption, compared with eating fruits regularly, eating rarely had a higher risk of multimorbidity (OR = 2.33, 95%CI: 1.90-2.85). Conclusions Sociodemographic indices (age, BMI, family history of hypertension, and family history of diabetes) and behavioral indices (fatigue status and fresh fruit consumption) increase the risks of multimorbidity. This study provides a necessary route to prevent and control multimorbidity in northeast China.